Reduced Basis Approaches in Time-Dependent Non-Coercive Settings for Modelling the Movement of Nuclear Reactor Control Rods (Communications in Computational Physics, 2018)
In this work, two approaches, based on the certified Reduced Basis method,have been developed for simulating the movement of nuclear reactor control rods, intime-dependent non-coercive settings featuring a 3D geometrical framework. In particular,in a first approach, a piece-wise affine transformation based on subdomainsdivision has been implemented for modelling the movement of one control rod. Inthe second approach, a "staircase" strategy has been adopted for simulating the movementof all the three rods featured by the nuclear reactor chosen as case study. Theneutron kinetics has been modelled according to the so-called multi-group neutrondiffusion, which, in the present case, is a set of ten coupled parametrized parabolicequations (two energy groups for the neutron flux, and eight for the precursors). Boththe reduced order models, developed according to the two approaches, provided avery good accuracy compared with high-fidelity results, assumed as "truth" solutions.At the same time, the computational speed-up in the Online phase, with respect to thefine "truth" finite element discretization, achievable by both the proposed approachesis at least of three orders of magnitude, allowing a real-time simulation of the rodmovement and control.